Pengaruh Jenis Pelarut Pada Ekstraksi Asam Lemak Dari Mikroalga - Surani; Cahyo Puji Asmoro (Integrated Lab Journal, 2022)
Microalgae are lipid-producing microorganisms that have the potential to be developed as an alternative raw material for biodiesel production. To become biodiesel raw material, several stages of treatment must be carried out. One of the treatments that must be done is to extract the fatty acids contained in the microalgae. In this study, we wanted to find out which type of solvent was the best for extracting fatty acids from microalgae nanochloropsis. The extraction method used was sonication with variations in the length of time 30,60 and 90 minutes, then continued with maceration for 24 hours. The type of solvent used is hexane, methanol and chloroform. The selection of this type of solvent is based on the difference in the polarity of the solvent.